1940
DOI: 10.1139/cjr40a-006
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Heat of Manganese From 16° to 22° K

Abstract: A calorimeter is described for routine measurements of specific heats in the temperature region of liquid hydrogen and liquid helium. It is designed so that samples can be interchanged without disturbing the calibration of the thermometer, or the water equivalent of the calorimeter. The calorimeter has been used to measure the specific heat of manganese from 16° to 22° K. It was found that the atomic heat of this metal is given by the formula[Formula: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1952
1952
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Singular Fermi-surface effects first appear in third-order perturbation for the scattering probability of the electrons. Kondo chose the s-d exchange model introduced and used by Zener, 2 Kasuya, 3 and Yosida, 4 and showed that the scattering probability was logarithmically singular as the temperature approached zero, for electron energies close to the Fermi energy, in accord with the experimental data.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Singular Fermi-surface effects first appear in third-order perturbation for the scattering probability of the electrons. Kondo chose the s-d exchange model introduced and used by Zener, 2 Kasuya, 3 and Yosida, 4 and showed that the scattering probability was logarithmically singular as the temperature approached zero, for electron energies close to the Fermi energy, in accord with the experimental data.…”
Section: Introductionmentioning
confidence: 51%
“…For the cutoff M equal to juo, b is of the order of magnitude of one. Using (A9), (2.6), (2.9), (2.10),(3,2), and (3.7), we obtain the shift of the thermodynamic potentialA&v = _ (81/16) (J/fx 0 yz 2 cS(S+1) XN(0)Vbk 2 T 2 ln(fjL 0 /6kT). (3.9)The most singular contribution to the third-order shift in entropy isASM = + (81/8)(// M o) 3 3 2^0 S'+1) XN(0)Vbk 2 T ln(iao/6kT).…”
mentioning
confidence: 99%
“…Elson et al , Shomate , Kelley et al , Armstrong and Greyson‐Smith , Booth et al , Guthrie et al , and Martin and Heer have measured heat capacity of α‐Mn at low temperatures. In addition, there is experimental data for heat capacity of α‐Mn at intermediate and high temperatures by Kelley et al , Armstrong and Grayson‐Smith , and Franzosini et al .…”
Section: Review Of Experimental Datamentioning
confidence: 99%
“…u D , K method [12] 410 heat capacity measurements [13] 343.5 [14] 348 [15] 417 [16] 392 [20] 415 [17] 409 [43] 350 thermal expansion measurements [22] 380 AE 20 [26] 485 elastic moduli measurements [31] 438, T > 95 K neutron diffraction studies 536, T < 95 K [44] 370 thermal expansion and heat capacity measurement temperature of a-Mn was selected equal to 460 K as the initial value for this optimization, as proposed by Weiss and Tauer [8].…”
Section: Referencementioning
confidence: 99%
“…The IVB elements have relatively high melting temperatures (see Table 1 for a summary of the important physical properties (11)(12)(13)(14)(15)(16)(17)(18) of the IVB subgroup) and upon solidification crystallize into the body centered cubic (bcc) structure (3-phase). However, for these metals the bcc lattice is dynamically unstable at low temperatures and consequently they undergo a structural phase transformation of the martensitic (19,20) variety to the hep structure (a-phase) which then remains stable for all temperatures less than the transformation temperature ^ bcc* This structural change is accompanied by about a one percent change in volume (V^^^^ < vî^*^^^) .…”
Section: The Hep -» Bcc Structural Transformationmentioning
confidence: 99%